INSTITUTIONAL AND SEGMENTAL ASPECTS OF UKRAINE’S FINANCIAL MARKET DIGITALIZATION - SOROKA, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article deals with the development analysis of certain segments of Ukraine’s financial market in the context of digitalization processes. The positions of modern foreign and domestic scientists regarding the digitalization impact on economic and financial relations are outlined. The key disproportions of the financial market at the institutional and segmental levels are highlighted. In particular, at the institutional level – the long-term and unchallenged dominance of banks over non-banking financial institutions; absence or minimal development of certain types of financial institutions; weakness of stock exchanges and exchange infrastructure in general; low level of financial inclusion. At the segmental level – imbalances in the lending market development, insufficient volume of the corporate securities market; weakness of leasing lending segments, factoring services, etc. It is argued that in the post-war reconstruction of Ukraine, the financial market should become an effective mechanism for the distribution of capital, therefore it is important to conceptually change the emphasis in its development on the digital technologies basis. It has been established that nowadays, the participants of various segments of the financial market are adapting their own strategies to the digital economy’s requirements. However, the degree of such adaptation and digitization level of certain segments of the financial market of Ukraine differ significantly. These disparities largely determine the strategic prospects of various segments of the domestic financial market. A similar conclusion was made regarding the digitalization strategy of financial institutions in Ukraine. For many financial institutions, the digitization of operations has become one of the important competitive advantages, but there are other approaches - in particular, in terms of digital technologies’ use for unfair competition and systemic violations of the rights of investors and consumers of financial services.
Keywords: financial market; stock market; money market; securities market; financial institutes; financial institutions; digitization; digital technologies